Respuesta :

The recursive formula of h(n) is h(1) = 36 and h(n) = h(n -1) - 5

How to determine the recursive formula?

The function is given as:

h(n) = 41- 5n

Calculate h(1) and h(2)

h(1) = 41- 5(1)

h(1) = 36

h(2) = 41- 5(2)

h(2) = 31

Calculate the difference between h(1) and h(2)

d = 31 - 36

d = -5

This means that:

h(1) = 36 and h(n) = h(n -1) - 5

Hence, the recursive formula of h(n) is h(1) = 36 and h(n) = h(n -1) - 5

Read more about recursive formula at:

https://brainly.com/question/1275192

#SPJ1

ACCESS MORE